Comparison of genome-wide and phenotypic selection indices in maize - Môro, Gustavo Vitti [UNESP]; Santos, Mateus Figueiredo; de Souza Júnior, Cláudio Lopes (My University, 2019)
The objective of this study was to compare the selection of maize lines by genomic selection and phenotypic selection, performed on the basis of selection indices rather than on each trait separately. To achieve this, 256 plants of an F2 population (S1 lines) were genotyped with 177 microsatellite molecular markers. These lines were evaluated in experiments with replications, considering different traits, phenotypic means (PM) and means predicted from the effects of the molecular markers (GM) were obtained and, from these, different selection indices were estimated for each line. The results showed that the GM were estimated with good precision, with high estimates for correlations, coefficients of determination and accuracy between the GM and the PM. The estimates of the correlation coefficients varied from medium to high between the selection indices obtained from PM and GM, with PM and GM generated values showing the closest agreement for the index proposed by Mulamba and Mock. The occurrence of superior genotype coincidences was not high between PM and GM based selections for the different selection indices, but values close to the observed phenotypic values were found. The evaluation of the populations selection for the different strategies confirmed that there were differences among the selection indices used for both PM and GM for most of the traits evaluated, that in average their means did not differ for most of the traits, and both differed from the control population, confirming the efficiency of the genomic selection performed on the basis of selection indices.
Keywords: Correlation; Efficiency; Marker assisted selection; Response to selection; Zea mays L